GIS-Based assessment of groundwater quality for drinking purpose in northern part of Fars province, Marvdasht - Honarbakhsh, Afshin; Tahmoures, Mohammad; Tashayo, Behnam; Mousazadeh, Milad; Ingram, Benjamin R.; Ostovari, Yaser (IWA Publishing, 2019)
With increasing population and freshwater shortages worldwide, it is necessary to protect vital groundwater resources using innovative methods. The main objective of this study is to use a GIS-based approach with the Groundwater Quality Index (GWQI) to analyze groundwater quality in Marvdasht located in the semi-arid region of Iran. For this purpose, we used groundwater quality data that were collected in a five-year period (2010–2015). The most influential water quality parameters were determined by performing map removal sensitivity analysis. Mean maps of the groundwater parameters showed that total dissolved solid (TDS), electrical conductivity (EC) and total hardness (TH) were the most important parameters that exceed the maximum permissible limits for drinking water. The groundwater quality of the study area is generally desirable for drinking (GWQI = 71). The GWQI map indicated that groundwater was higher quality in northern regions of the study area. The GWQI also revealed that only 2% of the study area (11 km2) was below the low quality class. According to map removal sensitivity analysis, Mg2+, TH and Na+ were identified as the most sensitive water quality parameters. Therefore, these parameters need to be monitored regularly and with increased precision.
Keywords: GIS; groundwater quality; semi-arid region; sensitivity analysis